Relationship between Internet addiction and body mass index and the predictive role of emotion dysregulation - Azizi, Morteza; Abbasi, Behrouz; Aghaei, Hajar (Frontiers in Psychology, 2024)
In recent years, the widespread use of the Internet has led to increasing concerns about problematic behaviors related to excessive Internet use and their potential consequences. This study aimed to investigate the relationship between Internet addiction (IA), body mass index (BMI), and emotion dysregulation (ED). Specifically, the study aimed to determine if IA significantly predicts obesity and if both Internet addiction and obesity can be significantly predicted by ED. 367 school-attending adolescents (M age = 13.35; SD = 0.82; 49% girls) in Tekab participated in the study. Participants completed the Difficulties in Emotion Regulation Scale (DERS) and the Internet Addiction Test (IAT), while BMI was calculated using self-reported data to assess their obesity levels. The results indicated that ED significantly predicted both IA and increased BMI levels (p < .001). Furthermore, IA also significantly predicted elevated BMI levels (p < .001). Our findings showed that ED significantly predicted both higher IA and BMI values, while IA also significantly predicted elevated BMI levels These results have important implications for treatment. To address excessive internet use or overeating behavior in individuals with either condition, it may be necessary to target the underlying emotional dysregulation that contributes to the problem.